How to reduce fetal scalp blood sampling? A retrospective study evaluating the diagnostic value of scalp stimulation to predict fetal wellbeing assessed by scalp blood sampling. (August 2021) - Gilbert, M.; Ghesquiere, L.; Drumez, E.; Subtil, D.; Fague, V.; Berveiller, P.; Garabedian, C.
Abstract: Background: The Fetal Blood Sample (FBS) is used as an indicator of fetal acidosis during labor. Its place is discussed through the lack of randomized trials, as well as the limitations related to the technical procedure. An alternative could be the Fetal Scalp Stimulation (FSS). Aim: Our objective was to describe the FSS diagnostic value to predict fetal wellbeing defined from FBS. Methods: The FSS consisted in a digital scalp stimulation for 15 s. Test was negative when an acceleration and/or a normal variability were elicited in the 2 min following. FSS was performed before each FBS which was classified as normal when pH was > 7.25. The diagnostic value was assessed by sensibility, specificity, positive and negative predictive values. Findings: 148 women were included in our center from February to December 2019. Of the 191 FBS procedures, when accelerations were elicited sensibility was 58, 3 (36.8–77.1), specificity was 67, 5 (59.3–75), positive predictive value was 20, 9 (12.5–32.9) and negative predictive value was 91.7 % (95 %CI, 85–95.5). Discussion: FBS is considered as the gold standard in our study which could be discussed as it is abandoned in some countries because of its questioned reliability and the lack of controlled randomized trials. Conclusion: This study suggests that FSS could be an interesting alternative adjunctive test to perform in the first instance as it seems to be reliable, non-invasive and easy to perform in order to limit FBS only to absence of acceleration after FSS.